Valor nutricional das silagens de capim andropogon em três idades de corte - Gabriel de Oliveira Ribeiro Junior (2013)
This study was undertaken to evaluate the effect ofharvesting Andropogon gayanusgrass with 56, 84 and 112 d of regrowth on the nutritional value of the silages and methane emissions from sheep. To achieve this objective twotrials were performed: intake, digestibility and respirometry trial by sheep (experiment I) and in situdegradation kinetic of the silages (experiment II). A. gayanusgrass silage was made using 56, 84 and 112 days of re-growth in 200 L metallic barrels and fed to sheep (n=18) for a period of 21 days after which intake and digestibility were measured for 5 consecutive days. Net energy, energy balance and methane emissions were determined with an open circuit respirometry chamber. The animals stayed inside the chamber for 24 hours during feeding and fasting. The experimental design was completely randomized with three treatments (silage age) and six repetitions (sheep). The data were subjected to ANOVA and linear regression. There were no differences between the silages for dry matter (DM)(54.4 g/kg0.75 /d), organic matter (OM), neutral detergent fiber (NDF) and acid detergent fiber (ADF) intakes. However crude protein (CP) intake (g/kg0.75 /d) reduced (P <0.05) linearly with increasing A. gayanusgrass regrowth age. Silage DM apparent digestibility decreased linearly from 52.6 to 38.0% with increasing grass regrowth age. Apparent digestibility of OM and CP and true digestibility of NDF and ADF also decreased linearly (P<0.05) with increasing grass regrowth age. All treatments showed positive nitrogen (N) (g/d) balance and did not differ (P>0.05). Retained energy from rams decreased linearly from 37.2 to -0.1 kcal/kg0.75/d with increasing regrowth age. Silage digestible, metabolizable and net energies also decreased linearly (P<0.05) with increasing regrowth age. There were no differences (P>0.05) between methane emissions (g/kg of DM, g/kg of digestible DM and as % of gross energy intake) from rams fed silages with increasing A. gayanusregrowth age, and the averages were 11.6 g/kg of DM, 26.6 g/kg of digestible DM and 3.4% of gross energy intake. In experiment II the kinetics of ruminal DM, OM, CP, NDF and ADF degradation were evaluated. Dried and ground silage samples (5 mm) were incubated in nylon bags inside the rumen for 0, 6, 12, 24, 48, 72 and 96 h. The ruminal kinetic parameters of the silages from each treatment (56, 84 and 112 d of regrowth) in each animal (5 cows) were determined by the model: y = a + b(1 ec(tL)). The parameters generated by the model were analyzed as randomized block design, with grass regrowth age as fixed effect and animal as random effect (blocks). The grass silage ensiled with 56 days of regrowth had the highest (P<0.05) effective degradability of DM, NDF and ADF calculated for fractional rate of particulate passage of 2%/h.All silages evaluated had low CP solubility (<25.4%) and effective degradability (40.1%) calculated for fractional rate of particulate passage of 2%/h. The silages harvested with 84 and 112 d of regrowth had higher NDF and ADF lag times compared to the silage made with 56 dof grass regrowth. Increasing regrowth age reduced ruminal degradation, silage net energy and energy retention by the animals, therefore A. gayanus grass should be ensiled with 56 d of regrowth to produce silage with higher nutritional value. Grass regrowth age did not affect silages methane emissions (% of gross energy intake, g/kg of DM intake or g/kg digestible DM intake) by rams.